Transformative and troublesome: reflective blogging for professional learning about university teaching. Issue 4 (4th July 2018) - Smidt, Andy; Wheeler, Penny; Peralta, Louisa; Bell, Amani
ABSTRACT: The complexities of being an academic mean that there is often no time or space to reflect on teaching, and on academic life in general. In this study, four academics set up a private blog to share reflections on teaching. While initial commitment to the reflective blogging process was good, over time this declined. After 9 months of intermittent communication, we decided to wrap up the project and examine the experience. A qualitative analysis of the group's reflective posts and related emails revealed themes related to emotions, space and time in academic experience. We discuss why the blog space did not work as anticipated, and how such 'troublesome' spaces may, paradoxically, be viewed as transformative.